The bacterial translation stress response - Starosta, Agata L. (FEMS Microbiol Rev, 2014)
Throughout their life, bacteria need to sense and respond to environmental stress. Thus, such stress responses can require dramatic cellular reprogramming, both at the transcriptional as well as the translational level. This review focuses on the protein factors that interact with the bacterial translational apparatus in order to respond to and cope with different types of environmental stress. For example, the stringent factor RelA interacts with the ribosome to generate ppGpp under nutrient deprivation, whereas a variety of factors have been identified that bind to the ribosome under unfavorable growth conditions to shut-down (RelE, pY, RMF, HPF and EttA) or re-program (MazF, EF4 and BipA) translation. Additional factors have been identified that rescue ribosomes stalled due to stress-induced mRNA truncation (tmRNA, ArfA, ArfB), translation of unfavorable protein sequences (EF-P), heat shock induced subunit dissociation (Hsp15) or antibiotic inhibition (TetM, FusB). Understanding the mechanism of how the bacterial cell responds to stress will not only provide fundamental insight into translation regulation, but will also be an important step to identifying new targets for the development of novel antimicrobial agents.